Case report: Von Hippel-Lindau syndrome with multisystem involvement: a therapeutic dilemma - He, Shuai; Wang, Cong; Yang, Jing; Shen, Juan; Zeng, Xiaozhu; Zheng, Jun; Wang, Yongquan (Frontiers in Oncology, 2025)
We present a rare case of von Hippel-Lindau (VHL) syndrome type 2B, characterized by multisystem involvement including Stanford type B aortic dissection, pheochromocytoma, renal cell carcinoma (RCC), cerebellar hemangioblastoma with obstructive hydrocephalus, and extensive visceral cysts. This case highlights critical therapeutic dilemmas: urgent aortic repair versus risks of catecholamine surge from pheochromocytoma resection, and neurosurgical hazards of cerebellar lesions. We describe the diagnostic and therapeutic challenges associated with VHL syndrome, culminating in the development of a preliminary treatment strategy following multidisciplinary team (MDT) discussions. This study underscores the critical importance of early recognition and systematic MDT management to optimize clinical outcomes in VHL syndrome.